Salvianolic Acid B Reducing Portal Hypertension Depends on Macrophages in Isolated Portal Perfused Rat Livers with Chronic Hepatitis. (16th October 2012) - Zhao, Xin; Jia, Hongmei; Yang, Shijun; Liu, Yuetao; Deng, Bo; Xu, Xueyan; Zhang, Tao; Zhou, Hang; Zu, Chengzhe; Yin, He; Li, Ting; Song, Yijun; et al.
Abstract : This study is aimed to investigate the effects of Sal B on portal hypertension (PH). PH with chronic hepatitis was induced by carbon tetrachloride (CCl4 ) in rats. The model was confirmed with elevated portal pressures and increased serum CD163 levels. The inducible nitric oxide synthase (iNOS) or heme oxygenase-1 (HO-1) in portal triads was assessed. The isolated portal perfused rat liver (IPPRL) was performed at d 0, d 28, d 56, and d 84 in the progression of chronic hepatitis. After constricting with phenylephrine, the portal veins were relaxed with Sal B. The EC50 of Sal B for relaxing portal veins was − 2.04 × 10 − 9, 7.28 × 10 − 11, 1.52 × 10 − 11, and 8.44 × 10 − 11 mol/L at d 0, d 28, d 56, and d 84, respectively. More macrophages infiltrated in portal triads and expressed more iNOS or HO-1 as PH advanced. The areas under the curve (AUCs) of Sal B for reducing PH were positively correlated with the levels of iNOS or HO-1 in portal triads, and so did with serum CD163 levels. Sal B reduces PH in IPPRL with chronic hepatitis, via promoting portal relaxation due to macrophage-originated NO or CO in portal triads, partly at least.